ANALISIS PELAKSANAAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA KARYAWAN BAGIAN PRODUKSI PADA PT. PUTRA SUMBER UTAMA TIMBER JAMBI - Nippong Nippong (Jurnal Dinamika Manajemen, 2015)
This research was conducted at Timber PT. Putra Sumber Utama Jambi with the thesis title "Analysis of Employee Occupational Health and Safety Programs for Production at PT. Putra Sumber Utama Timber Jambiâ€. The purpose of this study is to describe and analyze the implementation of the Occupational Health and Safety program for production employees at PT. Sumber Utama Timber Jambi). The analysis used is descriptive analysis, which describes and describes and understands the implementation of health and occupational health programs. And based on the operational variables studied regarding the Occupational Health and Safety program for employees in production at PT. Sumber Utama Timber Jambi, namely regarding human aspects, aspects of equipment and equipment, aspects of K3 facilities and aspects of the work environment. Based on the results of research conducted by the author, that the implementation of the Occupational Safety and Health program in terms of human aspects, aspects of equipment and supplies, aspects of K3 facilities and aspects of the work environment have been carried out very well, this is in accordance with the respondents' responses to the statements given from various aspects above. Suggestions that can be given are that it is hoped that companies will pay more attention to the application of working hours, machine conditions, availability of polyclinics and cleaning facilities that are given to employees who get good grades.